Determinants of unplanned pregnancy among women: A case of Awach Health Centre IV in Gulu district. - Okae, Norman; Namagga, Jane Kasozi; Nambooze, Grace (Student's Journal of Health Research Africa, 2021)
Background: Planning of pregnancy is a pertinent public health practice that every woman should embrace at her reproductive age. It is considered a major necessity in adopting a healthier lifestyle before pregnancy that leads to positive maternal-child health outcomes. On the contrary, unplanned pregnancy is ranked among the major public health problems that predispose women to huge mortality and morbidity mainly through criminal/unsafe abortion coupled with poor post-abortion care. Methodology: We used descriptive designs, employing qualitative approaches. We purposely selected 10 participants who lived within Aswa County, to participate in the study. Data were collected using an in-depth interview. Interpretive content analysis was used to generate categories and themes. Results: The study generated four themes namely: individual determinants, family determinants, community determinants, and health facility determinants of an unplanned pregnancy. Conclusion and Recommendations: This study has contributed substantially in revealing determinants of an unplanned pregnancy. In Awach Health Centre IV, the determinants of unplanned pregnancy are sexual desires, prostitution, school-going status, income level, number of sexual partners, amenorrhea, marital status, contraceptives usage, religion, domestic violence, family planning discussion with husband. Others are; breastfeeding status during conception, the gender of existing children, recurrent obstetrical complications, distance from husband, rape, peer pressure, denial of pregnancy by men, type of settlement, contraceptive failure, and lack of sensitization. There is a need for a multi-level approach to address determinants of unplanned pregnancy ranging from individuals, families, communities, and health facilities approach. Improvement in the economic status of women, and implementing programs that encourage education of women/girl child could reduce unplanned pregnancy
Keywords: Determinants; Unplanned pregnancy; Among women; Awach Health; Centre IV; Gulu district